Formulasi Media Tumbuh Acetobacter xylinum Dari Bahan Limbah Cair Tempe dan Air Kelapa Untuk Produksi Nata De Soyacoco - Muhammad Alwi; Andi Lindhemuthianingrum; Umrah Umrah (Biocelebes, 2011)
The impact of tempeh liquid-waste (Limbah Cair Tempe, LCT) as Contaminant has become a serious environmental problem. This study was design as an alternative problem solving related to that issue. Combination of tempeh liquid-waste and coconut water (Air Kelapa, AK) can be utilized as a medium of nata de soyacoco production. This research was aimed to obtain the best medium formulation for Acetobacter xylinum in order to produce the bacterial cellulose. This experiment was arranged in completely randomized design with 6 treatments and 3 replications. The treatments were P0 (LCT 0% + AK 0%), P1 (LCT 0% + AK 100%), P2 (LCT 25% + AK 75%), P3 (LCT 50% + AK 50%), P4 (LCT 75% + AK 25%), and P5 (LCT 100% + AK 0%). Parameters observed in this experiment were the days appear of nata, thickness, fresh weight, rendement and texture of nata which tested organolepticly. The best medium formulation for nata de soyacoco production was P4 (LCT 75% + AK 25%), which resulted 1.04 cm thickness, 139.48 gram fresh weight, 42.27% rendement and 1.7 of texture value. Key words: tempeh liquid water, coconut water, Acetobacter xylinum.